"What We've Got Here Is Failure to Communicate": The Need for Crisis Communication Skills Training in Public Health Graduate Programs. - Kelly, Patrick J. A.; Bass, Sarah Bauerle (American Journal of Public Health, 2026)
The article discusses the critical need for enhanced crisis communication and media relations training in public health graduate programs to address the erosion of public trust in science, particularly highlighted during the COVID-19 pandemic. It notes that current curricula lack specific competencies in these areas, leaving public health professionals unprepared to effectively communicate scientific information to diverse audiences during crises. The authors advocate for integrating crisis communication training into accredited public health programs to equip future professionals with the skills necessary to convey clear, accurate messages and rebuild public confidence in health authorities. They emphasize the importance of adapting communication strategies to the evolving media landscape and fostering partnerships with communities to enhance message credibility and relevance.